Prevalence and factors associated with breast milk donation in banks that receive human milk in primary health care units - Tatiana Mota Xavier de Meneses; Maria Inês Couto de Oliveira; Cristiano Siqueira Boccolini (Brazilian Society of Pediatrics, 2017)
Objective: To estimate the prevalence and to analyze factors associated with breast milk donation at primary health care units in order to increase the human milk bank reserves. Methods: Cross‐sectional study carried out in 2013 in Rio de Janeiro, Brazil. A representative sample of 695 mothers of children younger than 1 year attended to at the nine primary health care units with human milk donation services were interviewed. A hierarchical approach was used to obtain adjusted prevalence ratios (APR) by Poisson regression with robust variance. The final model included the variables associated with breast milk donation (p ≤ 0.05). Results: 7.3% of the mothers had donated breast milk. Having been encouraged to donate breast milk by healthcare professionals, relatives, or friends (APR = 7.06), receiving information on breast milk expression by the primary health care unit (APR = 3.65), and receiving help from the unit professionals to breastfeed (APR = 2.24) were associated with a higher prevalence of donation. Admission of the newborn to the neonatal unit was associated with a lower prevalence of donation (APR = 0.09). Conclusions: Encouragement to breast milk donation, and information and help provided by primary health care unit professionals to breastfeeding were shown to be important for the practice of human milk donation.